Perbedaan Kinerja Karyawan Pabrik Kelapa Sawit (PKS) Timur PT. Perkebunan Nusantara IV Ditinjau dari Tipe Kepribadian Introvert dan Ekstrovert - Salsabilah Alfira; Dalimunthe Hairul Anwar (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2022)
This paper aims to determine the differences in employee performance in terms of introvert and extrovert personality types. Problems focused on employee performance and personality type. In order to approach this problem, the theoretical reference from Wirawan (2009) is used for aspects of employee performance and the theory from Carl Jung for indicators of introverted and extroverted personality types. Nusantara IV Plantation. The number of samples in this study were 60 employees with the sampling technique used was total sampling. The data were collected through a screening test to see personality types, and employee performance data from company data and analyzed qualitatively. In line with the discussion in the theoretical basis, the hypothesis proposed in this study is that there are differences in employee performance in terms of introverted and extroverted personality types with the assumption that the performance of extroverted personality type employees is higher than that of Introverted personality type employees. Based on the results of the analysis carried out, the results obtained that the hypothesis was rejected. The results of data analysis through the one way ANOVA test showed sig (p) = 0.100 where the criteria p: 0.05 then it was stated that there was a difference or vice versa. The normality test was declared normal with a value of 0.137. The homogeneity test of this study was 0.165 and was declared homogeneous. The empirical mean of performance on the extrovert personality type is 23.80, and the empirical mean of the introverted personality type is 22.60. This study concludes that there is no difference in employee performance in terms of introverted and extroverted personality types so that the proposed hypothesis is rejected and the performance of extroverted personality type employees has a higher average value than introverts.